2020
DOI: 10.1101/2020.06.17.20133579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GLUCOCOVID: A controlled trial of methylprednisolone in adults hospitalized with COVID-19 pneumonia

Abstract: Background. We aimed to determine whether a 6-day course of intravenous methylprednisolone (MP) improves outcome in patients with SARS CoV-2 infection at risk of developing Acute Respiratory Distress Syndrome (ARDS). Methods. Multicentric, partially randomized, preference, open-label trial, including adults with COVID-19 pneumonia, impaired gas exchange and biochemical evidence of hyper-inflammation. Patients were assigned to standard of care (SOC), or SOC plus intravenous MP [40mg/12h 3 days, then 20mg/12h 3 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 25 publications
3
68
0
5
Order By: Relevance
“…After screening 7285 titles and abstracts and 122 full texts, 32 unique randomised controlled trials were identified that evaluated drug treatments as of 20 July 2020 (fig 1). 30313233343536373839404142434445464748495051 Searches of living evidence retrieval services identified one additional eligible randomised controlled trial 52. Eighteen randomised controlled trials have been published in peer reviewed journals, and 14 only as preprints.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After screening 7285 titles and abstracts and 122 full texts, 32 unique randomised controlled trials were identified that evaluated drug treatments as of 20 July 2020 (fig 1). 30313233343536373839404142434445464748495051 Searches of living evidence retrieval services identified one additional eligible randomised controlled trial 52. Eighteen randomised controlled trials have been published in peer reviewed journals, and 14 only as preprints.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 32 included drug trials, six evaluated treatment against active comparators, 18 evaluated treatment against standard care or placebo, and two evaluated different durations or doses of the same treatment. Our analyses were performed on 26 June 2020 and include 20 randomised controlled trials 3134353637383941424344454647484950Table 1. presents the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 26 These results are consistent with and add validation to multiple recently published randomised and cohort studies from Italy, Spain and the USA showing an association of corticosteroid treatment with decreased mortality and need for ventilators. 27–29 …”
Section: Therapeutic Response To Corticosteroids In Op and Covid-19mentioning
confidence: 99%